THE RISE OF THE PLATFORM ECONOMY IN THE INFORMATION AGE AND ITS EFFECTS ON WORK:: FLEXIBILITY, PRECARIZATION AND REPERCUSSIONS OF UBERIZED WORK IN PORTUGAL - Grillo Gomes Dambrós, Nirsan; Lima do Ó, Juliete (Revista Gênero e Interdisciplinaridade, 2021)
In this study, we discuss the most relevant aspects concerning the new labor context of uberization, aiming to: i) correlate the advancement of Industry 4.0, together with the new Information and Communication Technologies and the dissemination of the internet in the so-called Information Age, with the consolidation and expansion of the Platform Economy; ii) analyze the theoretical debate about labor relations on digital platforms, highlighting issues related to their function, some of the mechanisms involved in the phenomenon and their respective dynamics; iii) analyze the relevant aspects that hover over the legal and labor framework of workers linked to digital platforms in Portugal, in a context of algorithmic subordination, bringing to light the main legal repercussions in the context of work uberized in Portugal. From this perspective, the discussion presented below is based on scientific articles with a qualitative approach, journalistic articles, as well as works by important scholars in the world of labor.